The Influence of Islamic Branding and Culture on Sunan Ampel Purchasing Decisions: Positive Emotions as Mediator - Syehfuddin, Moch. Fahmi; Muzdalifah, Laily; Novie, Muhafidhah; Sholikhah, Afifatus (Airlangga Journal of Innovation Management, 2025)
This study aims to analyze the effect of Islamic Branding and Culture on purchasing decisions in Sunan Ampel religious tourism in Surabaya, with positive emotions as a mediating variable. This study uses a quantitative approach with an accidental sampling technique, which is sampling based on chance, where anyone who accidentally meets the researcher and meets the criteria as a respondent will be sampled. This study involved 130 respondents who were Sunan Ampel Surabaya religious tourism visitors. Data collection was done through online questionnaires, and data analysis was carried out using SmartPLS 4 software to test the relationship between the variables studied. The results showed that Islamic Branding positively and significantly influences visitor purchasing decisions. In addition, Culture has also been proven to have a significant positive influence on purchasing decisions. This study also found that consumers' positive emotions can significantly mediate the effect of Islamic Branding on purchasing decisions. However, different results were found on the culture variable, where positive emotions did not significantly mediate the influence of Culture on purchasing decisions. This finding shows the important role of emotions in strengthening the influence of Islamic Branding, but does not apply equally in cultural contexts. This research has implications for the development of Islamic Branding and Culture in influencing Purchasing Decisions with the role of Positive Emotions, especially in the development of existing marketing theories. The results of this study can also be a guideline or rationale for consumers in making purchasing decisions related to Islamic Branding and Culture.